Association between serrated epithelial changes and colorectal dysplasia in inflammatory bowel disease - Parian, Alyssa (Gastrointest Endosc, 2015)
BACKGROUND AND AIMS: Serrated epithelial change (SEC) is a histologic finding in longstanding colitis that may be associated with dysplasia. Our primary aim was to determine the incidence of dysplasia and colorectal cancer (CRC) in inflammatory bowel disease (IBD) patients with SEC. Secondary aims were to determine the rate of location concordance between SEC and dysplasia/CRC and to identify other risk factors associated with dysplasia in IBD patients with SEC. METHODS: A retrospective, descriptive, observational study was performed by searching the Pathology Data System at a single tertiary referral center for a histologic finding of “serrated epithelial change.” The patient’s first pathology specimen with SEC was designated the index SEC. All subsequent pathology reports were evaluated for the occurrence and location of dysplasia or CRC. Univariable and multivariable logistic regression were performed to identify predictors of dysplasia. RESULTS: There were 187 patients with confirmed IBD and 1 or more histologic findings of SEC without prior dysplasia. Mean IBD duration was 16 years, and median follow-up time was 28 months. The rate of high-grade dysplasia or CRC was 17 per 1000 patient-years. Thirty-nine of 187 patients (21%) had synchronous or metachronous dysplasia or CRC. Location concordance was 68%. Multivariable analysis found SEC on follow-up examinations, older age at IBD diagnosis, male gender, and a first-degree relative with CRC were associated with dysplasia in IBD patients with SEC. CONCLUSIONS: This uncontrolled study describes a high frequency of dysplasia in patients with a histologic finding of SEC. SEC seen on successive endoscopic examinations further increased the risk of dysplasia. Further controlled studies are needed to determine if SEC is a precancerous lesion in IBD patients and if SEC can be endoscopically identified. (Gastrointest Endosc 2016;84:87-95.)